Exploring the Antimicrobial and Antioxidant Properties of Silybum marianum Tissue-cultured Phenolic Extracts - Al-Hamdany, Islam Yasir Abdullah; Mohammed, Muthanna Jasim; Al-Taei, Shifaa Mahdi Salih (Journal of Multidisciplinary Applied Natural Science, 2025)
This study contributes to understand the medicinal properties of Silybum marianum L., commonly known as milk thistle. The result demonstrates the plant’s antioxidant and antibacterial activities have the potential to significantly impact the fields of botany, pharmacology, and medicine. The study was initiated by culturing different parts (root, stem, cotyledonary leaves, and leaves) on a Murashige and Skoog (MS) medium supplemented with benzyl adenine (BA) and naphthalene acetic acid (NAA) for callus induction. One of the key findings of this study is the effectiveness of the 0.5 mg L-1 BA and 2.0 mg L-1 NAA combination for callus initiation. As revealed by the results, this combination was the most effective among the various combinations tested. The study involved extracting the explants: the leaf, cotyledon, stem, root, callus of the leaf, and cotyledon of S. marianum L. The extraction process used a hexane solvent to remove fat. An ethanol solvent for phenolics separation after hexane was applied to the same sample. The high-performance liquid chromatography (HPLC) results showed that all the explants contain various phenolic compounds. The antibacterial activity has also been identified at 200 µg/mL concentrations against four pathogenic bacterial strains: Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus by using the agar dilution method. The results showed significant cotyledonary leaf callus extract showed antibacterial activity, notably against E. coli, with a zone of inhibition measuring 31 mm. These extracts were also used as antioxidants. The root extract has antioxidant activity with a percentage of 79.0%. These extracts and their compounds could be used as a natural antioxidant and antibacterial source. As we unravel the full potential of plant tissue culture and the conventional antibiotics and antioxidants become less effective and the side effects of synthetic compounds rise, exploring plant-based solutions like those from the tissue culture of S. marianum could provide valuable and eco-friendly alternatives, and contribute to developing novel therapeutic agents from natural sources.